Encountering God: Mysticism and the "dark night" in the works of Edith Stein - Arickal, Justin (Teresianum, 2025)
Edith Stein focuses on the topic of mysticism in the later stages of her scholarly work. In Wege der Gotteserkenntnis (WGE) and Kreuzeswissenschaft (KW) she reflects on the writings of Pseudo-Dionysius the Areopagite and John of the Cross respectively. Although the two writings differ in various ways, this article suggests that WGE and KW can be read in a complementary manner in order to address the question of how God can be encountered and whether the cross can be a point of encounter with God. A closer examination of Edith Stein's works on mysticism reveals a particular line of thought. A complementary analysis shows that Stein identifies three ways of knowing God: the way of reason, the way of faith, and the way of supernatural, mystical experience (= WGE). To progress on the way of mystical experience, one may also experience a so-called "dark night", which is a way of taking up one’s cross (= KW). As painful as this experience may be, it can also be interpreted as a process of letting go of self-centered desires and fixed expectations of God. Thus, such a transformative process can lead to a paradigm shift from self-centeredness to God-centeredness, in which God is sought for His own sake. Such a God-centeredness can culminate in a form of mystical union. Edith Stein’s final days in Auschwitz can be read as the lived closing chapter of Kreuzeswissenschaft.